Dream nation : Puerto Rican culture and the fictions of independence - Acosta Cruz, María, 1956- (Latinidad., 2014)
Over the past fifty years, Puerto Rican voters have roundly rejected any calls for national independence. Yet the rhetoric and iconography of independence have been defining features of Puerto Rican literature and culture. In the provocative new book Dream Nation, María Acosta Cruz investigates the roots and effects of this profound disconnect between cultural fantasy and political reality. Bringing together texts from Puerto Rican literature, history, and popular culture, Dream Nation shows how imaginings of national independence have served many competing purposes. They have given authority to the island's literary and artistic establishment but have also been a badge of countercultural cool. These ideas have been fueled both by nostalgia for an imagined past and by yearning for a better future. They have fostered local communities on the island, and still helped define Puerto Rican identity within U.S. Latino culture. In clear, accessible prose, Acosta Cruz takes us on a journey from the 1898 annexation of Puerto Rico to the elections of 2012, stopping at many cultural touchstones along the way, from the canonical literature of the Generación del 30 to the rap music of Tego Calderón. Dream Nation thus serves both as a testament to how stories, symbols, and heroes of independence have inspired the Puerto Rican imagination and as an urgent warning about how this culture has become detached from the everyday concerns of the island's people. A volume in the American Literature Initiatives series.